The Evolution and Contemporary Relevance of Administrative Law in Modern Government Governance - Aufial Hidayat; Aldri Frinaldi (Journal of Social Research, 2025)
The development of modern governance demands fundamental reforms in State Administrative Law (HAN) to be able to respond to the dynamics of bureaucratic digitalization and demands for public accountability. This study aims to analyze the development and relevance of HAN in the context of modern governance based on the principles of good governance . The research method used is a qualitative normative through library research on legal literature, legislation, and previous research results indexed by SINTA and having a DOI. The results show that HAN is transforming from a traditional bureaucratic paradigm to a digital government system that is adaptive to technological innovation, while still maintaining the general principles of good governance (AUPB). HAN reform in Indonesia is increasingly relevant with the presence of regulations such as Law Number 30 of 2014 concerning State Administration which emphasizes legal certainty, protection of citizens' rights, and the administrative responsibilities of public officials. In a global context, the emergence of the New Public Analytics (NPA) paradigm demands a reinterpretation of the principles of legality and accountability, especially regarding the use of artificial intelligence in public decision-making. This study concludes that the relevance of HAN in the modern era of governance lies in its ability to integrate legal values with the principles of digital transparency, public participation, and protection of citizens' administrative rights.